الاستنباط عند المطهر بن علي بن محمد الضمدي، 1048 هـ. في تفسيره "الفرات النمير في تفسير الكتاب المنير" - العلي، نورة بنت عبدالعزيز بن محمد; الضعيان، أشواق بنت عبدالعزيز بن سعد (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2021)
العلامة الضمدي من أعلام القرن الحادي عشر الهجري، وله مؤلفات في علوم عدة، الاهتمام بالاستنباط من القرآن الكريم واستخراج الفوائد والمعاني من آياته العظام من أهم مقاصد المفسرين في تفاسيرهم ومن أعظم العلوم التي اشتغلوا بها بعد التفسير، استخدم الضمدي صيغا تدل على مواضع الاستنباط، وهي: وفيه دليل، والآية تدل على، وفي ذكر كذا دليل على، وفي الآية دليل، فيه إيماء، وفيه إشارة، تنوع أسلوب الضمدي في صياغة الاستنباط، فاستعمل ألفاظا توحي بأن ما يعقبها استنباطا بلفظ بليغ وسلاسة في العبارة، وإيجاز في الكلمة، تنوعت الاستنباطات عند الضمدي فشملت فنونا عدة وعلوما شتى، كالاستنباطات العقدية، والاستنباطات الفقهية، والاستنباطات الأصولية، والاستنباطات التربوية والسلوكية، غالب استنباطات الضمدي صحيحة وموافقة لمنهج أهل السنة والجماعة، إلا واحدا تبع فيه بعض المفسرين فوقع في المحذور، استخدم الضمدي في استنباطاته عدة دلالات لتوصله إلى المعنى الصحيح، ومن هذه الدلالات الاستنباط بدلالة التركيب، الاستنباط بدلالة النص (مفهوم الموافقة)، الاستنباط بدلالة المفهوم (مفهوم المخالفة، الاستنباط بدلالة الإشارة (دلالة الالتزام)، الاستنباط بدلالة الاقتران، انفرد ببعض الاستنباطات التي لم أجد من وافقه عليها.
Al-Allamah Al-Damadi is one of the flags of the eleventh century AH, and he has books in several sciences. The interest in deducing from the Holy Quran and extracting the benefits and meanings from his great verses is one of the most important purposes of the commentators in their interpretations and among the greatest sciences that they worked with after the interpretation. There is evidence in it, and the verse indicates that, and in mentioning such an evidence and in the verse there is evidence, in which there is a gesture, and there is an indication. When Al-Damadi included many arts and various sciences, such as doctrinal deductions, jurisprudential deductions, fundamentalist deductions, educational and behavioral deductions, most of Al-Damdi's deductions are correct and agree with the approach of Ahl al-Sunnah wa al-Jamaa'ah, except for one in which some commentators followed and fell into the forbidden. These connotations are inference in terms of syntax, inference in terms of the text (the concept of consent), inference in terms of the concept (the concept of contravention, inference in terms of the sign (the significance of commitment), inference in terms of conjugation He was singled out for some conclusions, which I could not find who agreed with.
Keywords: القرآن الكريم -- التفسيرات القرآنية -- الاستنباطات العقدية -- دلالة الالتزام